The Influence Of Corporate Governance on the Performance of Islamic Banks in Indonesia - Yulfiswandi, Yulfiswandi; Hesniati, Hesniati; Elida, Shelly (Universitas Ibn Khladun Bogor, 2024)
This research was conducted with the aim of testing the influence of Corporate Governance on the performance of Sharia Banks. The measurement used to measure this independent variable is to analyze the total size of the board, audit committee, non-executive directors, sharia board and risk management committee. Quantitative data is used as research data by looking at the annual report of the company concerned. Sharia Bank is used as the object of this research. The sample was determined using a purposive sampling method and resulted in 13 Sharia Commercial Bank companies. The annual report for the 2018-2022 period is used as processed data obtained from the official website of the company concerned. This research analysis uses panel regression of company data. This research uses five independent variables consisting of Board Size, Non-Executive Directors, Audit Committee, Shariah Board, and Risk Management Committee. The dependent variable in this research is sharia bank performance which is measured using ROA (Return On Assets) and ROE (Return On Equity). This research uses panel regression. The F test results in this study were 0.014378 for ROA measurements and 0.0000 for ROE measurements. The adjusted R square test results are 0.282995 for ROA and 0.729184 for ROE. The conclusion of this research is that the board size variable obtained insignificant results. The non-executive director variable for ROA measurement shows significant results, while the ROE measurement is not significant. The audit committee variable obtained insignificant results. The sharia board variable produces insignificant results and the risk management committee variable produces insignificant results. The author was limited in completing this research because the researcher only used the Islamic banking sector, so in selecting the sample the data obtained was relatively small. Recommendations from researchers that can be given to other prospective researchers are to be more detailed in assessing the performance of Islamic banks. You can expand the independent and dependent variables